PACIFIC SOLUTION POLICY: MENGGUGAT TANGGUNG JAWAB AUSTRALIA DALAM PENANGANAN PENGUNGSI - Natalia Yeti Puspita; Annisa Irina Nur Halima (Jurnal Paradigma Hukum Pembangunan, 2020)
As one of the countries which is ratifying the 1951 Refugeee Convention and the 1967 Protocol, Australia has an obligation to protect refugees and guarantee their rights as stated in the provisions. With the issuance of the Pacific Solution Policy by the Australian Government to restrict refugees who come to Australia, Australia has reneged on international treaties on the protection of refugees that have been ratified. Based on the results of normative juridical research which is used in this paper, it can be seen that the state sovereignty principle which is used as the legal basis for implementing the policy cannot necessarily erase the obligations that have been imposed on it, especially with the development of the current understanding of the state sovereignty principle that links human rights protection. In addition, the attachment to international agreements that have been agreed based on the principle of Pacta Sunt Servanda becomes the basis for strengthening legitimacy that the Australian Government can be held responsibility in connection with the implementation of the Pacific Solution Policy in the handling of refugees in Australia.